Mobile Application Category Cybercrime To Filter The Content Using Ontology - Kintani M A; Rizal U (International Conference on Engineering and Technology Development (ICETD), 2017)
The current Internet is growing rapidly. This has created new opportunities in various fields which we can think of, be it entertainment, business, sports or education. The Internet is a useful way for people to do business effectively, very fast. It saves a lot of time, money and resources. Unfortunately, it is also an open invitation to fraudsters and online scams becoming more rampant. Like two sides of a coin, the Internet also has its own drawbacks. One of the major disadvantages is Cybercrime - illegal activities on the Internet. Computers today are being misused for illegal activities such as e-mail fraud, credit card fraud, spam, piracy of software and so forth, which violates privacy.  Cybercrime is a crime where a criminal act can only be done with the use of cyber technology and occur in the cyberworld. (M.Yoga.P,2013).The ontology is defined as a formal and clear picture of conceptualization together. (Gruber 1993). Frantz and Franco (2005) argued that ontology provide shared and common understanding of the domain to be notified between people and computers to facilitate knowledge sharing and reuse. In addition, Frantz and Franco explained that ontology provides a clear formal conceptualization (ie the meta-information) that describes the semantic information of the arrest of a static domain knowledge-based systems.Ontology is proposed to collect, examine, analyze, prepare for, obtain and store evidence of computer crime in cyberspace. To answer the above conditions and problems, then here I do resume journal entitled  "Analysis and Classification of Cybercrime with OntologyMethod"